The Application of Problem Solving Reasoning (PSR) in Improving Students’ Metacognitive at the Twelfth Grade Students of SMAN 19 Makassar - Sujarwo, Sujarwo; Akhiruddin, Akhiruddin; Salemuddin, Muh. Reski; Sabillah, Bellona Mardhatillah; Sriwahyuni, Sriwahyuni (Universitas Malikussaleh, 2019)
The study describes the students’ thinking skill, and metacognitive in problem solving reasoning (PSR) learning model at SMAN 19 Makassar in the academic year 2018/2019. The design of this research was Classroom Action Research (CAR) in which subject was students social science eleventh grade students that consisted of 69 students. Data were collected by using a problem-solving reasoning tests in the form of multiple choice, essay, oral and practice tests. Data of problem solving reasoning (PSR) abilities were analyzed quantitatively and qualitatively. The results of this study show that: (1) The application of problem solving reasoning (PSR) can improve the statistical students’ metacognitive of social science eleventh grade students. In cycle I, the students’ English outcomes average reached 59.2, whereas in cycle II was successfully increased into 84.8, In cycle I, the students’ sociology and anthropology outcomes average reached 60.9, whereas in cycle II was successfully increased into 88.5 and in cycle I, the students’ Art and Culture outcomes average reached 62.3, whereas in cycle II was successfully increased into 86.9. (2) The application of problem solving reasoning (PSR) can improve students' metacognitive of social science XI grade students. These results indicate that there has been an increasing in percentage mastery learning by 20% from cycle I to cycle II.